Cost-effectiveness of umeclidinium/vilanterol combination therapy compared to tiotropium monotherapy among symptomatic patients with chronic obstructive pulmonary disease in the UK. Issue 1 (December 2015) - Punekar, Yogesh; Roberts, Graeme; Ismaila, Afisi; O'Leary, Martin
ABSTRACT Background The cost-effectiveness of umeclidinium bromide-vilanterol (UMEC/VI) versus tiotropium monotherapy in the UK was assessed using a UMEC/VI treatment-specific economic model based on a chronic obstructive pulmonary disease (COPD) disease-progression model. Methods The model was implemented as a linked-equation model to estimate COPD progression and associated health service costs, and its impact on quality-adjusted life years (QALYs) and survival. Statistical risk equations for clinical endpoints and resource use were derived from the ECLIPSE and TORCH studies, respectively. For the selected timeframe (1–40 years) and probabilistic analysis, model outputs included disaggregated costs, total costs, exacerbations, life-years and QALYs gained, and incremental cost-effectiveness ratios (ICERs). Results Random-effects meta-analysis of tiotropium comparator trials estimated treatment effect of UMEC/VI as 92.17 mL (95 % confidence interval: 61.52, 122.82) in forced expiratory volume in 1 s. With this benefit, UMEC/VI resulted in an estimated annual exacerbation reduction of 0.04 exacerbations/patient and 0.36 life years gained compared to tiotropium over patient lifetime. With an additional 0.18 QALYs/patient and an additional lifetime cost of £372/patient at price parity, the incremental cost effectiveness ratio (ICER) of UMEC/VI compared to tiotropium was £2088/QALY. This ICER increased to £17, 541/QALY when price of UMEC/VI was increased to that of indacaterol plus tiotropium in separate inhalers. The ICER improved when model duration was reduced from patient lifetime to 1 or 5 years, or when treatment effect was assumed to last for 12 months following treatment initiation. Conclusion UMEC/VI can be considered a cost-effective alternative to tiotropium at a certain price.